Autonomia dos enfermeiros de referência de um hospital universitário federal - Alba, Naiana Buligon (2020)
As a result of the adhesion of the Federal University Hospitals (HUF) to the Brazilian Hospital Services Company (EBSERH) and a new organization chart in their administrative structure, there was a need due to the role and the responsibility performed by nursing, the need to create a new intermediate position between senior management and employees, called the reference nurse, who develops management, care, team and unit functions. This study aims to analyze the autonomy of the nurses of reference of a HUF in the management of EBSERH. It is a descriptive-exploratory field research, with a qualitative approach. The population consisted of 16 reference nurses from a University Hospital in the interior of Rio Grande do Sul / Brazil. Data collection took place in September and October 2019, using the semi-structured interview method. Data processing was carried out according to Minayo's thematic analysis (2014), consisting of pre-analysis, material exploration, treatment and interpretation of results. Ethical precepts were respected according to resolution 466/12 of the National Health Council. The results of this study allowed us to glimpse that the reference nurses recognize having autonomy in their daily work. The facilitators of autonomy consist of a good relationship with the head of the area, recognition of the nursing team, professional appreciation and mutual performance between assistance and administration. The study participants also spoke about inherent skills for the development of autonomy in the reference nurse in the hospital environment, they are: professional identity; administrative management; care management and people management. It is concluded that the position of reference nurse has great importance within the institution with regard to the administration of the nursing team and inter-relationship with the multidisciplinary health team. In addition, this professional expands the quality of care offered by the institution, while elaborating care strategies based on the real needs of patients arising from their contact with them during the exercise of care.